Evaluation of the Arabic Language Learning Implementation and Challenges Faced in the Foreign Language Intensification Program (PIBA) - Firdaus, Muhammad; Usman, Syahruddin; Abunawas, Kamaluddin; Ibrahim, Misykat Malik; Haniah (Institut Agama Islam Negeri Curup, 2025)
This study aims to evaluate the implementation of the PIBA program at UIN Alauddin Makassar, with a specific focus on Arabic language instruction. The evaluation covers key components such as instructional procedures, supporting facilities, student engagement, and the challenges encountered throughout the program. Employing a qualitative approach and field research methods, the study involved leaders, instructors, and third-semester PIBA students as participants. The findings showed that Arabic language teaching within the PIBA program employed a range of instructional methods and models. Although lecture and discussion formats facilitated student interaction, the limited use of interactive strategies such as simulations and technology integration reduced active student participation. Moreover, the instructional materials were not sufficiently adapted to address the diverse needs of students, indicating the necessity for more flexible and competency-based modules. Time constraints during classroom sessions also hindered in-depth exploration of the content. Based on these findings, the study recommends innovations in teaching approaches through the integration of technology, the development of adaptive learning resources, and improved time management to enhance program effectiveness. Periodic evaluations are also considered essential for ensuring continuous improvement in Arabic language education at UIN Alauddin Makassar and for positioning it as a relevant instructional model in the digital era.